Application of betacyanins pigments from Alternanthera brasiliana as yogurt colorant - Schneider Teixeira, Aline (2022)
Betacyanins are betalain derivatives showing a red-violet color suitable as a natural food colorant. An aqueous extract rich in betacyanin pigments and phenolic compounds from Alternanthera brasiliana was characterized using a high-performance liquid chromatography system with diode array and electrospray mass spectrometry detection. The major betacyanins (amaranthine, isoamaranthine, betanin and isobetanin, celosianin II and isocelosianin II) were identified and quantified. Eleven peaks were analyzed for phenolic compounds grouped into hydroxycinnamic acids and flavones. Different plant extract concentrations were added to freshly prepared set type yogurts (350, 700, and 1400 μL/80 g yogurt). Color properties in CIELAB space, pH, total phenolic content, and ferric reducing antioxidant power were analyzed on yogurts during storage time. The evolution of pigments and polyphenolic compounds during cold storage was studied by HPLC-ESI-QTOF-MS screening.The extracted color showed to be stable at the yogurt pH range. When added to yogurts, a natural berry-like color was achieved. These results provide a natural plant pigment-based alternative for application in food products, being the first time that A. brasiliana is used as a colorant in a dairy product. Besides color, polyphenols input turns Alternanthera brasiliana extract into a desirable functional food ingredient.